2021
DOI: 10.3390/plants10122554
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Major Phenolic Compounds of Seeds, Skins, and Pulps from Various Vitis spp. and the Effect of Powdery and Downy Mildew Diseases on Their Levels in Grape Leaves

Abstract: The main purpose of this study is to determine the contents of 3 major phenolic compounds (gallic acid, catechin, and epicatechin) in 22 different grape cultivars/hybrids obtained from 2 different breeding programs. Additionally, changes in these phenolic components in the grape leaves of some resistant/tolerant species were determined in relation to powdery and downy mildew diseases in viticulture. The skin, pulp, and seeds of grape berries were analysed over two years, while changes in the phenolic contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Romero-Pérez et al [ 94 ] showed that the content of trans-resveratrol was considerably increased in grape berries infected with powdery mildew, and the degree of infection was positively related to their stilbene content. Naturally mildew-infected grape berries and leaves exhibited an increase in cis-resveratrol and catechin [ 26 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Romero-Pérez et al [ 94 ] showed that the content of trans-resveratrol was considerably increased in grape berries infected with powdery mildew, and the degree of infection was positively related to their stilbene content. Naturally mildew-infected grape berries and leaves exhibited an increase in cis-resveratrol and catechin [ 26 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the broad interest in more sustainable agriculture, metabolomics studies performed so far have focused on understanding the mechanism of grapevine defense against downy mildew, while only a limited number of investigations focused on E. necator ( Pimentel et al., 2021 ). Recent studies have shown the mechanisms underlying the synergy between metabolomics and various omics approaches ( Maia et al., 2020 ; Pimentel et al., 2021 ; Sosa-Zuniga et al., 2022 ; Yin et al., 2022 ), the metabolic differences in the composition of the berries and leaves in several grapevine cultivars ( Atak et al., 2021 ; Rienth et al., 2021 ) as well as control of the pathogen ( Gur et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a relationship between increased resistance in plants and high content of phenolic compounds that play an important role in plant resistance to plant pathogens. The role of these compounds in plant resistance to fungal pathogens is prominent (Atak et al, 2021). Heim et al (2002) reported that the beneficial effects of phenolic compounds have been attributed to their antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%